Pengaruh Modifikasi Edukasi Dengan Senam Hipertensi Terhadap Pengetahuan Dan Tekanan Darah Lansia - Ramadhani, Muhammad Naufaludin; Parawansa, Nabila Indar; Wibowo, Nia Cahayani Putri; Sanjayani, Tutut Putri; Megawati, Riris Risca; Fajarani, Dratia Eka (Jurnal Keperawatan Florence Nightingale, 2025)
Hypertension in the elderly is an important global health problem that, if not managed properly can cause serious complications. In Indonesia, the prevalence of hypertension tends to increase with age, especially among the elderly. Hypertension can be treated with pharmacological and non-pharmacological therapy, one of which is through hypertension exercise. This study aims to determine the effect of hypertension exercise modification and education by distributing leaflets on the knowledge and blood pressure of the elderly in the Chronic Disease Management Program (Prolanis) of the Halmahera Health Center UPTD. The method used is quantitative with a pre-posttest design. The population used was all Prolanis patients, with sample selection using simple random sampling, namely 20 respondents. Data were collected using a questionnaire with blood pressure measurements before and after the hypertension exercise intervention. The results of the study showed that hypertension exercise had a significant effect on decreasing diastolic blood pressure (p = 0.001), but did not have a significant effect on decreasing systolic blood pressure (p = 0.130). Providing education through leaflets did not show a significant effect on increasing the knowledge of the elderly (p = 0.398). Based on these findings, hypertension exercise has been proven effective as one of the interventions in managing hypertension in the elderly, although education through leaflets did not show significant changes in knowledge. This study is expected to provide contributions in the development of hypertension management in the elderly.